2021
DOI: 10.5751/es-12167-260201
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the potential of vulnerability assessments for managing social-ecological systems

Abstract: The concept of vulnerability has broadened from initial applications in the fields of risk and hazards, human ecology and resilience to include the management of social-ecological systems (SES). We review how this concept has been operationalized in various contexts and identify opportunities and challenges to apply vulnerability assessments to SES management in the face of social, environmental, and climatic changes. We synthesize these lessons into a 12-step framework to help practitioners scope, design, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 128 publications
(198 reference statements)
0
16
0
Order By: Relevance
“…In coastal communities, resilience to external shocks relies on adaptive capacity, defined as the “latent ability to implement effective responses to changes by minimizing, coping with, or recovering from the potential impacts of a stressor” [84] , and the ability to turn surprises into opportunities to evolve, renew, learn, and increase adaptive capacity [43] . Resilience in small island communities relies on adaptive capacities that include flexibility and diversity in livelihood strategies, multilevel governance systems that are participatory, and adaptive local knowledge systems ( [1] , [6] , [14] ).…”
Section: Introductionmentioning
confidence: 99%
“…In coastal communities, resilience to external shocks relies on adaptive capacity, defined as the “latent ability to implement effective responses to changes by minimizing, coping with, or recovering from the potential impacts of a stressor” [84] , and the ability to turn surprises into opportunities to evolve, renew, learn, and increase adaptive capacity [43] . Resilience in small island communities relies on adaptive capacities that include flexibility and diversity in livelihood strategies, multilevel governance systems that are participatory, and adaptive local knowledge systems ( [1] , [6] , [14] ).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that satellite monitoring and perception surveys of various stakeholder groups can support each other in evaluating the performance of MPAs. Thus, it appears that we possess the legal, technical and conceptual tools to protect marine biodiversity via LSMPAs, which work as long as stakeholder involvement is duly considered [105][106][107]. The point is to use these tools.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the vulnerability assessment framework outlined by Marshall and colleagues [ 46 ] and Thiault and colleagues [ 47 ] to investigate the vulnerability of fishing communities ( Fig 1 ). We first determine ecological risk, a combination of the ecological exposure and ecological sensitivity of target species to changing climate conditions ( Table 1 , Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%